2022
DOI: 10.18295/squmj.4.2021.062
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Profile of Stroke Patients Presenting to the Emergency Department of a Major Stroke Centre in Oman

Abstract: Objectives: Stroke is a significant public health problem and one of the important preventable non-communicable diseases. Preventive stroke programs are yet to be properly established in Oman, with a better focus on increasing awareness among those who are currently at risk. This study was conducted to describe the characteristics of stroke presenting to a tertiary care hospital in Oman. Methods: This was a cross-sectional hospital-based study. Included 193 stroke cases which were prospectively recruited from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
1
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 31 publications
1
1
1
Order By: Relevance
“…The fact that many of our patients had poor blood pressure management caused by non-adherence to treatment due to cost and drug availability certainly increased the significance of hypertension control. As noted in this study, diabetes mellitus ranked second on the list of risk factors as did other hospital studies around the world [7,[17][18][19][20][21][22][23][24][25][26].…”
Section: Vol 1 | Issue 2 | Jul -Dec 2022supporting
confidence: 55%
“…The fact that many of our patients had poor blood pressure management caused by non-adherence to treatment due to cost and drug availability certainly increased the significance of hypertension control. As noted in this study, diabetes mellitus ranked second on the list of risk factors as did other hospital studies around the world [7,[17][18][19][20][21][22][23][24][25][26].…”
Section: Vol 1 | Issue 2 | Jul -Dec 2022supporting
confidence: 55%
“…Harthietal. 28 found higher rates of hypertension as the most prevalent risk factor (72.5%) followed by DM (54.4%) when compared with this study, Itagietal. 29 reported hypertension in 38% cases followed by hypertension with diabetes mellitus in 23%.…”
Section: Discussioncontrasting
confidence: 54%
“…Similar male predominance was observed in other studies from Asia when compared with European and North American studies. 28,29 Hypertension was the most common risk factor in all the studies relating to SICH. Feldmann et al have reported a relative risk of 3.9 for ICH in patients with hypertension.…”
Section: Discussionmentioning
confidence: 99%